Association of Pre-gestational Overweight and Obesity with Cesarean Section Delivery - Sara K. M. Rahman; Osman Mohammad Qadir (Academic Journal of Clinicians, 2022)
Background: Pre-pregnancy overweight and obesity showed to have significant impact on pregnancy outcomes and cesarean section. Nonetheless, this association still need further clarification. Objective: To assess the association between maternal pre-pregnancy overweight and obesity as risk factor for cesarean section. Patients and Methods: This was a case control study conducted during a period of 18 months from 2018 through 2020 included 100 Sudani women who were delivered by cesarean section and 100 women delivered vaginally. Both groups almost matched for their demographic and obstetrical characteristics . Frequency of overweight and obesity was measured in both groups and compared. Estimation of risk was performed according to odds ratio. All statistical tests applied accordingly at 0.05 level of significance. Results: In Cesarean section group 32% of women were overweight 32% and 27% obese . In group 2, 20% overweight and 16% obese, the prevalence of pre-gestational overweight obesity was significantly higher in cesarean section group than controls (virginal delivery) group, (P. value = 0.004), women with pre-pregnancy overweight or obesity were about 2.6 fold more likely to be delivered by cesarean section than pregnant women who were not overweight or obese (odds ratio = 2.6). Conclusion: Pregestational overweight and obesity increase the risk of completing a pregnancy by cesarean section more than twice compared to those of normal weight. And they are independent risk factors for cesarean section